Dynamics and Control of a Stop Rotor Unmanned Aerial Vehicle - Alvaro Vargas-Clara; Sangram Redkar (International Journal of Electrical and Computer Engineering (IJECE), 2012)
The objective of this work was to develop a variety of control systems for a Stop-Rotor Unmanned Aerial Vehicle (UAV) in hover flight. The Stop-Rotor UAV has capabilities of Vertical Take-off and Landing (VTOL) like a helicopter and can convert from a helicopter mode to an airplane mode in mid-flight. Thus, this UAV can hover as a helicopter and achieve high mission range of an airplane. The stop-rotor concept implies that in mid-flight the thrust generating helicopter rotor stops and rotates the blades into airplane wings. The thrust in airplane mode is then provided by a pusher propeller. The aircraft configuration presents unique challenges in flight dynamics, modeling and control. In this paper a mathematical model is derived, and then the model is simulated with non-zero initial conditions. Various control systems are then implemented. The control techniques utilized are a linear control, optimal linear control and a nonlinear control with the objective of stabilizing the UAV in hover flight. Settling time and control effort are then compared across the different control systems.DOI:http://dx.doi.org/10.11591/ijece.v2i5.1589